Kardiochirurgia dorosłychIntraoperative assessment of cardiac ventricular function in coronary artery surgery by transoesophageal echocardiography using tissue Doppler imaging - Goździk, Anna; Goździk, Waldemar; Stachurski, Andrzej; Płońska-Gościniak, Elżbieta (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Intraoperative transoesophageal echocardiography, during surgical coronary revascularization, enables almost on- line assessment of regional contractility and ejection fraction of right and left ventricle. Tissue Doppler imaging seems to be a more precise method of cardiac function imaging. Aim: The aim of the study was to evaluate systolic and diastolic left and right ventricular function in patients undergoing cardiac surgical revascularization with (CPB) and without cardiopulmonary bypass (OPCAB). Monitoring of cardiac function was performed with intraoperative transoesophageal echocardiography using the traditional technique and tissue Doppler imaging. Material and Methods: 30 patients scheduled for first time elective surgical coronary revascularisation were included in the prospective study. The patients were previously qualified by the surgeon to be operated on with CPB (n=20) or OPCAB (n=10). Ejection fraction (EF) of left and right ventricle was counted. Visual examination of regional function of left and right walls was performed. Diastolic function was assessed by registration of early (E) and late (A) velocity of mitral and tricuspid inflow. E/A ratio and deceleration time (Dt) of early velocity (E) were also counted. Doppler tissue imaging was used to measure the following parameters: e – early diastole velocity, a – late diastole velocity, and s – systolic velocity. Index e/a and deceleration (dt) of velocity e were also calculated. All the measurements were done twice: before revascularization, early post induction to anaesthesia and after revascularization, before closure of the sternum. Results: Better systolic and diastolic right ventricular function was noted in the OPCAB group. CPB impairs right more than left ventricular function. Examinations done with TDI confirmed the greatest sensitivities and accuracy of this technique. Conclusions: Doppler tissue imaging seems to be a more sensitive and precise method for echocardiographic evaluation of cardiac function. The study performed was considered as preliminary, and we decided to continue the observation on a larger group of patients.